Genome-wide, high-resolution DNA methylation profiling using bisulfite-mediated cytosine conversion - Reinders, Jon; Delucinge Vivier, Céline; Theiler, Grégory; Chollet, Didier; Descombes, Patrick; Paszkowski, Jerzy

(untitled) (Genome Research, 2008)
Methylation of cytosines (mC) is essential for epigenetic gene regulation in plants and mammals. Aberrant mC patterns are associated with heritable developmental abnormalities in plants and with cancer in mammals. We have developed a genome-wide DNA methylation profiling technology employing a novel amplification step for DNA subjected to bisulfite-mediated cytosine conversion. The methylation patterns detected are not only consistent with previous results obtained with mC immunoprecipitation (mCIP) techniques, but also demonstrated improved resolution and sensitivity. The technology, named BiMP (for Bisulfite Methylation Profiling), is more cost-effective than mCIP and requires as little as 100 ng of Arabidopsis DNA.